The Influence of the Location of Pertamina Mandalika International Street Circuit on the Decision to Visit Lombok Through Lombok International Airport, West Nusa Tenggara - Edelwistin Erningpraja; Annike Resty Putrie (CV. Rayyan Dwi Bharata, 2023)
There are four media that are the strategy of the Indonesian government in promoting its tourism within the framework of the 'Wonderful Indonesia' branding, namely online media, electronic media, print media and space media. This research looks at how the influence of the location of the Pertamina Mandalika Internasional street circuit has on the decision to visit Lombok via Lombok International Airport, NTB. As well as how much influence the location of the Pertamina International Street Circuit has on the decision to visit Lombok via Lombok International Airport, NTB. This research is a quantitative research, data sources used are primary data and secondary data. The population of this study were passengers using a sample of 100 respondents, with data collection techniques: surveys, literature studies, and instrument tests. The data analysis technique used: simple linear regression, T test, and the coefficient of determination, which was processed using SPSS version 22. The value (a) or a constant of 8.562 this value indicates that at the Pertamina Mandalika Internasional Street Circuit (X) Location it was worth 0 or not increases, then the Visit Decision (Y) will still be worth 8.562. the regression coefficient value (b) is 0.611 (positive) which shows a unidirectional effect, which means that if the Pertamina Mandalika International Street Circuit Location is increased by one unit, it will increase the Visit Decision by 0.611 units. With a sig value (0.000) ≤ (0.05), which means the location of the Pertamina Mandalika International Sreet Circuit has an influence on the interest in visiting Lombok through Lombok International Airport. The location of Pertamina Mandalika International Street Circuit contributes 62.6% to the interest in visiting Lombok through Lombok International Airport and the remaining 37.4% is influenced by other factors which are not summarized in this study. The results showed that the Pertamina Mandalika International Street Circuit location variable had a significant influence on the interest in visiting Lombok through Lombok International Airport, NTB.